2021
DOI: 10.1088/1361-6528/abd20a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the accumulation of aptamer AS1411 and verapamil conjugated silver nanoparticles in tumor cells to enhance the radiosensitivity of glioma

Abstract: Radioresistance significantly decreases the efficacy of radiotherapy, which can ultimately lead to tumor recurrence and metastasis. As a novel type of nano-radiosensitizer, silver nanoparticles (AgNPs) have shown promising radiosensitizing properties in the radiotherapy of glioma, but their ability to efficiently enter and accumulate in tumor cells needs to be improved. In the current study, AS1411 and verapamil (VRP) conjugated bovine serum albumin (BSA) coated AgNPs (AgNPs@BSA-AS-VRP) were synthesized and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Results also showed that AsNPs had better radiation sensitization than AgNPs and PEGylated AgNPs (PNPs) and induced a higher apoptosis rate. Meanwhile, Zhao et al 35 also designed AgNPs coated with AS1411, verapamil (VRP) and bovine serum albumin (BSA) (AgNPs@BSA-AS-VRP). The results showed that the mixture of AgNPs@BSA-AS and AgNPs@BSA-AS-VRP (19 : 1) could significantly accumulate in tumor cells, and the corresponding SER value was 1.55, which significantly improved the therapeutic effect of radiotherapy.…”
Section: Precious Metal-based Nanoradiosensitizersmentioning
confidence: 99%
“…Results also showed that AsNPs had better radiation sensitization than AgNPs and PEGylated AgNPs (PNPs) and induced a higher apoptosis rate. Meanwhile, Zhao et al 35 also designed AgNPs coated with AS1411, verapamil (VRP) and bovine serum albumin (BSA) (AgNPs@BSA-AS-VRP). The results showed that the mixture of AgNPs@BSA-AS and AgNPs@BSA-AS-VRP (19 : 1) could significantly accumulate in tumor cells, and the corresponding SER value was 1.55, which significantly improved the therapeutic effect of radiotherapy.…”
Section: Precious Metal-based Nanoradiosensitizersmentioning
confidence: 99%
“…34 Similar to Au nanoparticles, noble metal nanomaterials with other high-Z elements (e.g., Pt and Ir) have been developed to enhance the efficacy of RT. [35][36][37] For example, Muhammad et al found that HeLa cells treated with dendritic Pt nanomaterials showed a sharp decline in their survival curve when compared with the control group under X-ray irradiation. 38 In addition to the most commonly used high-energy X-rays, some other radioactive sources are also used in tumor RT, such as protons and neutrons.…”
Section: Multifunctional Nanomaterials As Radiosensitizers For Radiot...mentioning
confidence: 99%
“…For example, As1411 is a guanine-rich DNA aptamer with high specificity and affinity to nucleolin receptors which are only overexpressed on the plasma membrane of cancer cells. The specific interaction between As1411 and nucleolin has been used to mediate the highly specific targeting of radiosensitizers to cancer cells [ 126 , 127 , 128 , 129 ]. As1411-conjugated gold nanoparticles [ 128 ], gold nanoclusters [ 126 ], or silver nanoparticles [ 127 , 129 ] have been proved to be capable of acting as efficient radiosensitizers for cancer targeting treatment.…”
Section: Affinity Ligands and Corresponding Applications In Radiotherapymentioning
confidence: 99%